Emerging markets and sovereign risk - Finch, Nigel (Palgrave Macmillan, 2015)
"Emerging markets are an increasingly important area of corporate strategy and fast becoming the driver of global growth. Today, emerging markets account for 40% of global GDP and are experiencing growth rates two or three times faster than developed economies. Not surprisingly, investment activity in emerging market jurisdictions has been frenetic with developed-world firms having invested more than $3 trillion, making it one of the biggest corporate investment cycles since the railway boom of the 19th century. Emerging Markets and Sovereign Risk provides case studies, commentary and analysis of investment and financial aspects of emerging market investment from international experts inside Standard & Poor's, Moody's, global investment funds, corporations and academia, and covers keys issues such as credit rating agencies and the rating process, risk assessment and pricing of sovereign debt, challenges related to foreign direct investment in emerging countries, capital flows in frontier, emerging and less-mature economies, structuring debt and equity investments in 'non-investment grade' countries, key value drivers in emerging market asset classes, sovereign wealth funds and emerging market investment, and considerations in the management of sovereign credit ratings"..